2020
DOI: 10.1111/php.13194
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection by Workwear: Ultraviolet Protection Factors for Artificial Radiation from Welding Arcs

Abstract: Photoprotection by clothing is one of the most effective protective measures against solar ultraviolet radiation (UVR), and the related concept of UV protection factors (UPF) for fabrics has proven itself for decades. Although immense work has been carried out regarding factors influencing textile sun protection, the idea of UPFs for artificial UVR, if necessary with different action spectra, is payed little attention. In this work, a modified UPF equation is proposed utilizing welding arcs and the ICNIRP acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…TiO2 nanomaterial for UV protection textiles is one of the specialized uses of nanomaterials for protective textiles [70]. UV protection fabrics are required in these high ultraviolet radiation (UVR) hazard-prone industrial work environments [71]. UV protection fabrics can also be employed in other industrial sectors such as aircraft and automobiles [72].…”
Section: Polymeric Nano-emulsion In Ultraviolet (Uv)-protective Texti...mentioning
confidence: 99%
“…TiO2 nanomaterial for UV protection textiles is one of the specialized uses of nanomaterials for protective textiles [70]. UV protection fabrics are required in these high ultraviolet radiation (UVR) hazard-prone industrial work environments [71]. UV protection fabrics can also be employed in other industrial sectors such as aircraft and automobiles [72].…”
Section: Polymeric Nano-emulsion In Ultraviolet (Uv)-protective Texti...mentioning
confidence: 99%
“…For example, Wei 9 studied the effect of graphene coating on the thermal conductivity of welding protective clothing fabrics and found that graphene coating could reduce the temperature rise of the fabric about 30% from 27°C to 19°C. Stefan Bauer 10 conducted a series of analyses of light protection measures for welding protective clothing and proposed an improved method for welding protective clothing based on the idea of solar ultraviolet protection factor. Kim et al 11 evaluated the performance of materials for protective clothing used for welding in a hazardous shipbuilding work environment and found that among the materials selected, carbon dioxide/aramid blended fabrics appeared to be suitable for welding protective clothing.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the solar UV radiation, artificial UVR sources such as xenon arc or germicidal lamp, UVR emission from certain welding arc are significant. Therefore, UV protective textiles are also essential in these artificial significant UVR hazard industrial work areas [42]. Apart from these, UV protective textiles can be used for other industrial applications such as aerospace, automobile etc [43].…”
Section: Introductionmentioning
confidence: 99%